A Typology of Offenders Engaging in the Sex Trafficking of Juveniles (STJ): Implications for Risk Assessment. (September 2016) - Hargreaves-Cormany, Holly A.; Patterson, Terri D.; Muirhead, Yvonne E.; ,
Abstract: Psychopathy is highly prevalent within offenders who engage in the sex trafficking of juveniles (STJ) as 75% (n = 27) of offenders with sufficient data to assess the PCL-R (n = 36) met the criteria for psychopathy (n = 24 with a score of ≥ 30) and/or were close to the threshold (n = 3 with a score of 29.5) and 25% (n = 9; M = 26.78) exceeded the average score of North American adult male inmates (Patterson et al., 2013). Latent class analyses (LCAs) were conducted on 117 STJ offenders with data derived from protocols including demographics of the offenders and victims and various aspects of the nature of the criminal act(s) perpetrated by the offender focused upon the STJ offense(s). The LCA indicators were the STJ Scales measuring Criminal History Severity, Violence Severity, Criminal Sophistication and Charismatic Offender Behavioral Style. The second author's expertise from the field and interviews with victims and offenders were utilized to substantiate the findings. Two broad types of STJ offenders emerged: 1- Aggressive/Antisocial and 2- Charismatic/Manipulative with subtypes. The STJ Risk Scale scores suggested that Violent Charismatic/Manipulative STJ Offenders posed the greatest danger to society. Enhanced understanding of STJ offenders especially in regards to risk assessment may result in reduction of harm to juveniles.